Low Laser Therapy Plus Non-Surgical Periodontal Treatment Reduces Interleukin-1 Beta Serum Levels - Serena De Franceschi Maria; Giudice Amerigo; Pacifico Delfina; Crispino Antonio; Catalano Francesca; Michele Figliuzzi; Ventura Valeria; Di Fatta Concetta; Gulletta Elio; Leonzio Fortunato (Journal of Dentistry And Oral Implants, 2016)
Objectives: Periodontal disease is associated to widespread systemic inflammation, and further to both cardiovascular morbidity and mortality. Data from intervention studies demonstrated the beneficial effects of periodontal therapy in reducing vascular diseases. The present study was aimed to explore whether low-level Laser therapy as an adjunct to scaling and root planning reduces serum levels of inflammatory cytokines. Material and Methods: Thirty patients were enrolled. All recruited participants underwent blood sampling and dental inspection for periodontal indexes measurement. Plaque index, gingival index and probing depth were employed as measures of periodontal disease. Afterwards, patients underwent scaling and root planning plus low-level Laser therapy. Inflammatory biomarkers and periodontal indexes were measured before treatment and twenty weeks after treatment. Results: Plaque index, gingival index and probing depth largely improved at the follow-up visit, resulting more than halved from the baseline. Furthermore, a significant reduction of serum interleukin-1 beta has been observed (1.1 SD 2.1 vs 0.5 SD 1.3, P = 0.04), whereas serum interleukin-6 levels remained substantially unchanged. Blood C-reactive protein levels decreased at the follow-up, but not reaching statistical significance. Conclusions: therapy addressed to a local improvement of periodontal disease gives a reduction of systemic inflammation, possibly beneficial for cardiovascular health.
Keywords: Periodontal diseases